Evaluating liver type fatty acid binding protein as a diagnostic and prognostic biomarker in metabolic dysfunction-associated steatotic liver disease in pediatric patients - Nadia Al Mazrouei; Mostafa Mohsen ElGharbawy; Mahitab Gamal; Shaimaa Emad; Amal Ahmed Mohamed; Osama Mohamed Ibrahim; Asim Ahmed Elnour; Marafi Jammaa Ahmed; Semira Abdi Beshir; Vineetha Menon; Sami Fatehi Abdalla; Ali Awadallah Saeed; et al. (PLoS ONE, 2025)
Background Metabolic dysfunction-associated steatotic liver disease (MASLD), is a common liver disorder, predicted to increase globally. Currently, non-invasive methods are proposed for the assessment of (MASLD). This study aimed to investigate the use of serum Liver Type Fatty Acid Binding Protein (L-FABP) concentration as a diagnostic and prognostic biomarker in pediatric MASLD patients and to evaluate its relationship with steatosis and fibrosis. Methods An observational, cross-sectional study on paediatric MASLD patients. Serum levels of L-FABP and hepatic biochemical markers were measured and analyzed. Statistical analyses evaluated the association between L-FABP and other markers, while logistic regression and ROC curves assessed its diagnostic accuracy. Results Serum L-FABP levels showed a significant difference between the MASLD and control groups (P < 0.0001). The results of logistic regression revealed that each one-unit elevation of L-FABP level was associated with 144.5% higher odds of being MASLD (95% CI: 129.3% − 167.8%). A receiver operating characteristics (ROC) curve was constructed to assess the diagnostic accuracy of L-FABP. The resulted area under the ROC curve (AUC) was 0.885. The cutoff value was 5.7 ng/ mL, with sensitivity of 72.73%, and a specificity of 93.62%. The results also showed that the odds ratio of progressing from stage F2 to F3 increases by 108.9% (95% CI: 87.2% − 141.4%) for each one-unit increase in serum L-FABP level. Conclusion L-FABP shows promise as a non-invasive biomarker for diagnosing and monitoring MASLD in pediatric patients. Its association with disease stages suggests its utility in assessing disease progression, particularly in advanced stages.